Translation of English Future Tense in the Novel And Then There Were None - Mahasari Braga; Vica Ananta Kusuma; Enggar Mulyajati (Smart Edu Center, 2024)
To be a good translator, having linguistic competence is a must. One of the linguistic competencies is the mastery of tenses, for instance future tenses in both the source language (SL) and target languages (TL). The aim of this research is to understand the similarities and differences in forms of future expression in English and Indonesian. The data source was obtained from dialogue or utterances in the novel And Then There Were None and the translated novel entitled Lalu Semuanya Lenyap. In addition, the author will also analyze various translation strategies used by translators in transferring future concepts of SL into TL. This research is descriptive research with qualitative methods. The research results show that English and Indonesian tend to express the future lexically. In the source text, future forms of expression are formed with the auxiliary words